(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The WEDUSEA project is a €19.6 million European wide joint venture between 14 partners spanning industry and academia from Ireland, the UK, France, Germany, and Spain that will culminate with a two-year, grid connected deployment of a 1MW rated oscillating water column (OWC) wave energy converter (WEC) at the EMEC test site in Orkney, Scotland, UK. The WEDUSEA project will incorporate a number of novel systems and control strategies to improve device performance, annual power production, and grid integration. During the initial planning and design phases of the project, a wave-to-wire numerical model has been created to investigate the impact these new systems will have on device performance and allow for the testing and development of the control strategies necessary to operate the 1MW power take-off (PTO) system as efficiently as possible. This paper will detail the novel systems added to the OWC, the control strategies developed for the new additions, and the modelled performance of the OWC. The WEDUSEA OWC will rely on a Wells turbine for the pneumatic-to-mechanical conversion. As Wells turbines are susceptible to aerodynamic stall, a flow control system using 4 bypass valves of varying size will be added, and it will allow for up to 16 different variations for flow control. The performance of the valves will be tested via CFD and MATLAB-Simulink modelling. The nature of WECs result in fluctuations in the power delivered to the grid, and this can lead to undesirable impacts on the grid. To mitigate these power fluctuations, the WEDUSEA OWC electrical system will include a controllable super capacitor energy storage system that will be used to improve the power quality of the electricity delivered. The objective will be to absorb power peaks and use that stored energy to minimise energy troughs. The power output is aimed to be levelized by mitigating fluctuations in a certain frequency range. The ability of the super capacitor to improve power delivery to the grid may also facilitate improved performance and increased annual power production by the mechanical PTO by enhancing the turbine-generator control system flexibility. To incorporate the bypass valves and the super capacitor into the WEDUSEA OWC, more complex algorithms will need to be created for control of the mechanical and electrical components of the PTO. These algorithms will be tested and sharpened through testing using the wave-to-wire model developed using MATLAB Simulink and Simscape. The MATLAB-Simulink software simulations will allow for in-depth analysis of the impact the bypass valves will have on the behaviour of the pneumatic-to-mechanical section of the PTO. The Simscape Electrical software will allow for thorough modelling and evaluation of the electrical system and the impact the control strategies will have on the output power quality. The full model will allow for estimations of annual power production, and with improved kWh/yr, the LCOE could see significant reductions. The model testing and control development performed during this early stage of the project will help to maximise the deployment phase of the project and estimate annual power production.